A Multi-Time-Step Finite Element Algorithm for 3-D Simulation of Coupled Drift-Diffusion Reaction Process in Total Ionizing Dose Effect - Xu, Jingjie; Ma, Zhaocan; Li, Hongliang; Song, Yu; Zhang, Linbo; Lu, Benzhuo (IEEE transactions on semiconductor manufacturing, 2018)
In order to study the total ionizing dose degradation and enhanced low dose rate sensitivity effect for semiconductor devices in the space environment, we simulate the drift-diffusion-reaction processes in a 3-dimensional SiO 2 -Si system. Since the time scale of the drift-diffusion processes is much larger than that of the chemical reaction processes, we use a multi-time-step algorithm to calculate the two types of processes, respectively. In this paper, partial differential equations used to describe the electrodiffusion processes are solved by a finite element method, while the chemical reactions taking place independently in every mesh node are solved as ordinary differential equations. We reproduce qualitative properties of total ionizing dose effect and compare our numerical results with experimental data and other simulation results. This paper paves a way for 3-D simulation of total ionizing dose and enhanced low dose rate sensitivity with high efficiency and robustness.